A STUDY OF THE ELEMENTS FOR BUSINESS DEVELOPMENT IN THE THAI SPORTS INDUSTRY - Lakkhongkha, Kritsana (Academic Journal of Thailand National Sports University, 2024)
The purpose of this research was to study the key elements of the development of the sports industry in Thailand. It is qualitative research that collects data by in-depth interviews with experts in sports business. or related is an expert from government agencies involved in regulations and policies in sports in Thailand. Experts from national private organizations involved in sports. Executives from institutes and educational administrators in Thailand, totaling 9 people from purposive selection according to the qualifications specified. Experienced in the management of large corporations The sports business is an executive with more than 10 years of experience and an expert in academic fields with experience related to business development. Data were gathered with a structured interview. Data was conducts by gathering opinions that are relevant, consistent and useful for business development. Research results were found that for the development of the sport industry in Thailand There are four important components: Human resource capital. product development, business partner and competitive advantage.